The Indirect Effects of Proximal Stressors Associated with Posttraumatic Stress Symptoms Severity among Sexually Victimized Sexual Minority Women: A Cross-Sectional Path Analysis - Fergerson, Ava K. (Violence against women, 2024)
Sexual minority women (SMW) are at risk for sexual victimization and stressors specifically related to their minority identity (e.g., discrimination). However, SMW experience posttraumatic stress disorder (PTSD) at rates beyond what may be explained by elevated risk for sexual victimization alone. This study aimed to examine the impact of stigma on PTSD symptoms among SMW survivors of sexual victimization. Results indicate that in relation to minority-specific distal stressors (i.e., heterosexist experiences), both minority-specific and general proximal stressors (i.e., internalized heterosexism, negative posttraumatic cognitions) indirectly affected PTSD symptom severity among this cross-sectional sample of sexually victimized SMW.